Hot working forming method for platinum alloy electrode with multi-mode pore structure
Through the thermal processing and forming method of multimodal pore structure platinum alloy electrodes, the problems of low bond strength and poor electrocatalytic performance of existing platinum alloy electrodes are solved, and electrodes with high bond strength and electrocatalytic performance are achieved, meeting the needs of the new energy field.
Patent Information
- Application Number
- CN202411970106.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing platinum alloy electrodes have low bond strength, easy peeling, and poor mass transfer in high-precision applications, resulting in poor electrocatalytic performance and cannot meet the demand for high-end electrode materials in the new energy field.
The multimodal pore structure platinum alloy electrode is adopted to achieve the multimodal pore structure construction of the electrode through grading thermal processing, including the regulation of stepwise heat treatment, layer-by-layer spraying low-temperature heat treatment and high-temperature and high-pressure heat treatment.
The bonding strength and electrocatalytic performance of platinum alloy electrodes have been improved, and the development of long-life electrodes has been achieved, meeting the demand for high-end electrode materials in the new energy field.
Smart Images

Figure CN119747666A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode thermal processing, and in particular to a thermal processing forming method for a platinum alloy electrode with a multi-modal pore structure. Background Art
[0002] Platinum alloy electrode is an electrode material widely used in many electrochemical applications, and is favored for its excellent physical and chemical properties. Platinum and its alloys have excellent electrical conductivity and are suitable for various electrochemical reactions. Platinum alloys show extremely high corrosion resistance in a variety of chemical environments and can be used for a long time under harsh conditions such as strong acids and strong alkalis. Platinum alloy electrodes remain stable under high temperature and high pressure and are not easily oxidized or decomposed. Platinum alloys have good catalytic activity and can promote certain chemical reactions, especially in the fields of fuel cells and water electrolysis. Platinum alloys have high mechanical strength and toughness and can withstand certain mechanical stress and impact.
[0003] Platinum alloy electrodes are key components of proton exchange membrane fuel cells (PEMFCs) and are used to catalyze the reaction of hydrogen and oxygen. In the process of water electrolysis to produce hydrogen, platinum alloy electrodes serve as anodes and cathodes to promote the water decomposition reaction. Platinum alloy electrodes are widely used in various chemical sensors and biosensors, such as pH sensors, gas sensors, etc. In medical devices such as pacemakers and neurostimulators, platinum alloy electrodes are widely used due to their biocompatibility and corrosion resistance. In electroplating processes and electrochemical synthesis, platinum alloy electrodes are used to provide stable current and catalysis.
[0004] High-precision platinum alloy electrodes are a new generation of electrode materials after pure platinum electrodes. The existing technology often uses a room temperature spraying process to coat the slurry configured with platinum alloy powder on the middle layer and air-dry it to make an electrode. However, the electrodes obtained by this process have low bonding strength, are easy to peel off, and have poor mass transfer, resulting in poor electrocatalytic performance, which cannot meet the demand for high-end electrode materials in the new energy field. Therefore, graded heat processing is adopted to regulate the grain size and crystal surface ratio of the electrode material, optimize the pore structure of the electrode, and essentially improve the electrocatalytic performance of the electrode. In addition, regulating the composite process of the electrode, spraying low-temperature heat treatment layer by layer, and combining high temperature and high pressure heat treatment to realize the forming and manufacturing of a single electrode are inevitable strategies to ensure the bonding strength of the electrode. Summary of the invention
[0005] The purpose of the present invention is to provide a hot working forming method for a platinum alloy electrode with a multimodal pore structure, and to achieve the construction of a multimodal pore structure of the platinum alloy electrode by regulating the parameters of a step-by-step heat treatment process; and to achieve the development of a long-life platinum alloy electrode by combining layer-by-layer spraying of low-temperature heat treatment with high-temperature and high-pressure heat treatment.
[0006] To achieve the above object, the present invention provides a method for hot working of a platinum alloy electrode with a multimodal pore structure, comprising the following steps:
[0007] S1. Dissolve copper nitrate trihydrate and benzenetricarboxylic acid in deionized water and ethanol respectively, and disperse by ultrasonic for 0.5 h to prepare solution A and solution B;
[0008] S2, mixing the two solutions of step S1, ultrasonically mixing for 0.5 h, adding polyvinyl pyrrolidone dispersant, and further ultrasonically treating for 1 h to form solution C;
[0009] S3, transferring the solution C in step S2 into a 100 mL standard hydrothermal kettle, placing it in an oven, and heating it for 12 h. After the reaction is completed, naturally cool it to room temperature, centrifuge it for 10 min, collect the precipitate, wash it with a mixed solution of deionized water and ethanol, and heat dry it to obtain a blue metallic copper-based organic framework precursor powder;
[0010] S4, fully grinding the precursor powder of step S3 in a mortar, transferring it into a corundum boat, placing it in a tube furnace, introducing an inert gas, and performing high-temperature pyrolysis to obtain a black copper / carbon material powder;
[0011] S5, mixing the black copper / carbon material of step S4 with one of melamine, urea and dicyandiamide, transferring the mixture into a micro ball mill, grinding and mixing for 0.5 h to obtain a mechanical mixed material, placing the mixture in a tubular furnace, introducing an inert gas, and performing high temperature pyrolysis to obtain a black copper / nitrogen-carbon material powder;
[0012] S6, taking the copper / nitrogen-carbon material of step S5 and mixing it with sodium dihydrogen phosphate or sodium hypophosphite, transferring it into a micro ball mill, grinding and mixing it for 0.5h to obtain a mechanical mixed material, placing it in a tubular furnace, passing an inert gas, and performing high-temperature pyrolysis to obtain a black copper / nitrogen-phosphorus-carbon material powder;
[0013] S7, dispersing the copper / nitrogen phosphorus-carbon material obtained in step S6 in a mixed solution of deionized water and ethylene glycol or deionized water and ascorbic acid, ultrasonically dispersing for 0.5 h, adding potassium hypochlorous platinum or chloroplatinic acid, and further ultrasonically treating for 0.5 h to form a solution D;
[0014] S8, transferring the solution D in step S7 into a 100 mL standard hydrothermal kettle, placing it in an oven, and heating it for 12 h. After the reaction is completed, naturally cool it to room temperature, centrifuge it for 10 min, collect the precipitate, wash it with a mixed solution of deionized water and ethanol, and freeze-dry it to obtain a black platinum alloy material powder;
[0015] S9, dispersing the black platinum alloy material powder in step S8 in a mixed solution of deionized water and isopropanol, adding Nafion adhesive, ultrasonically treating three times, and further oscillating in a vortex agitator for 20 minutes to obtain a uniformly dispersed ink slurry containing platinum metal;
[0016] S10, spraying the ink slurry containing platinum metal in step S9 on the conductive carbon paper in batches and three times, and performing low-temperature drying to form a uniform catalytic layer;
[0017] S11, compounding the conductive carbon paper loaded with the catalytic layer in step S10 with the proton exchange membrane layer, and subjecting them to high temperature and high pressure treatment to form a platinum alloy electrode with a multimodal pore structure.
[0018] Preferably, in step S1, the mass ratio of copper nitrate trihydrate to benzenetricarboxylic acid is 3:2, and the volume ratio of deionized water to ethanol is 1:1; in step S2, the mass ratio of the added amount of polyvinyl pyrrolidone dispersant to copper nitrate trihydrate is 1:1; in step S3, the heating temperature is 140°C, the volume ratio of deionized water to ethanol is 1:1, and the drying temperature is 80°C.
[0019] Preferably, in step S4, the inert gas is argon, the high temperature pyrolysis is pyrolysis at 600°C for 2h, and the heating rate is 10°C / min.
[0020] Preferably, in step S5, the mass ratio of the black carbon material to one of melamine, urea and dicyandiamide is 1:1, the inert gas is argon, the high temperature pyrolysis is pyrolysis at 550-650°C for 4h, and the heating rate is 10°C / min.
[0021] Preferably, in step S6, the mass ratio of the copper / nitrogen-carbon material to sodium dihydrogen phosphate or sodium hypophosphite is 1:1.5, the inert gas is argon, the high-temperature pyrolysis is pyrolysis at 700-750°C for 2h, and the heating rate is 10°C / min.
[0022] Preferably, in step S7, the volume ratio of deionized water to ethylene glycol or ascorbic acid is 1:1.5-2, and the amount of potassium chloroplatinate or potassium hypochloroplatinate added is 5% of the mass of the copper / nitrogen phosphorus-carbon material.
[0023] Preferably, in step S8, the heating temperature is 120°C, the volume ratio of deionized water to ethanol is 1:0.5-1, and the freeze-drying temperature is -40°C.
[0024] Preferably, in step S9, the volume ratio of deionized water and isopropanol is 1:4, the mass fraction of Nafion adhesive is 5%, and the volume ratio of its addition amount to the polyvinyl pyrrolidone dispersant in step S2 is 1:0.01, and the ultrasonic treatment is performed for 0.5 h every 0.5 h, for a total of three times.
[0025] Preferably, in step S10, the platinum content in the ink slurry containing platinum metal is 0.15 mg pt / cm 2 The rotary spraying is as follows: the conductive carbon paper is placed in a rotary machine at 200 rpm and 40° C. for spraying with a spray gun, with an interval of 0.5 h, and spraying layer by layer for three times in total.
[0026] Preferably, in step S11, the area ratio of the catalyst layer to the proton exchange membrane layer is 1:1, and the high temperature and high pressure treatment is 130-150° C. and hot pressing at 10-13 MPa for 3-5 min.
[0027] The advantages and beneficial effects of the hot working forming method of the multi-modal pore structure platinum alloy electrode of the present invention are:
[0028] 1. The platinum alloy electrode forming process of the present invention adopts a graded heat processing treatment. First, the transition metal-based precursor is subjected to a carbonization heat treatment, then sodium dihydrogen phosphate or sodium hypophosphite is selected for mixed heat treatment, followed by layer-by-layer spraying low-temperature heat treatment, and finally a single electrode is formed and manufactured by high-temperature and high-pressure heat treatment.
[0029] 2. The platinum alloy electrode forming process of the present invention realizes the multimodal pore structure regulation of the electrode through graded heat treatment. First, the appropriate pore size regulating agent is selected, the proportion is regulated, and the heat treatment temperature is adjusted to realize the micro-, meso-, and macro-pore characteristics of the electrode microscopic pore structure. Secondly, low-temperature heat treatment is sprayed layer by layer to realize the layered pore structure construction of the electrode.
[0030] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 XRD patterns of the multimodal pore structure platinum alloy electrodes prepared in Examples 1-3 of the present invention, wherein (a) is Example 1, (b) is Example 2, and (c) is Example 3;
[0032] Figure 2 This is a pore size distribution diagram of the platinum copper / nitrogen phosphorus-carbon-600 electrode prepared in Example 2 of the present invention;
[0033] Figure 3 This is the SEAD diagram of the platinum copper / nitrogen phosphorus-carbon-600 electrode prepared in Example 2 of the present invention;
[0034] Figure 4 Polarization curve and peak power density curve of the platinum copper / nitrogen phosphorus-carbon-600 electrode prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0036] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0037] Unless otherwise defined, the reagents, equipment and other materials used in the present invention are conventionally commercially available.
[0038] Example 1
[0039] A hot working forming method for a multi-modal pore structure platinum alloy electrode comprises the following steps:
[0040] S1. Weigh 3.6 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and dissolve it in 16 mL of deionized water, and disperse it by ultrasonic for 0.5 h to form solution A. Weigh 2.4 g of benzenetricarboxylic acid (H3BTC) and dissolve it in 16 mL of ethanol, and disperse it by ultrasonic for 0.5 h to form solution B.
[0041] S2, mixing solution A and solution B in step S1, ultrasonically mixing for 0.5 h, adding 3.6 g of polyvinyl pyrrolidone dispersant, and further ultrasonically treating for 1 h to form solution C;
[0042] S3, transfer solution C into a 100mL standard hydrothermal autoclave, place it in an oven at 140°C, heat it for 12h, and after the reaction is completed, naturally cool it to room temperature, centrifuge it at 12000rpm for 10min, collect the precipitate, wash it with a mixed solution of 5mL deionized water and 5mL ethanol, wash it cumulatively 3 times, and dry it in an oven at 80°C for 8h to obtain a blue metallic copper-based organic framework precursor powder;
[0043] S4, taking 300 mg of the blue precursor powder from step S3, grinding it thoroughly in a mortar, transferring it into a corundum boat, placing it in a tube furnace, introducing inert gas argon (Ar), pyrolyzing it at 600° C. for 2 h, with a heating rate of 10° C. / min, to obtain a black copper / carbon material powder;
[0044] S5, taking 200 mg of the black copper / carbon material of step S4 and 200 mg of melamine, mixing them, transferring them into a micro ball mill, grinding and mixing for 0.5 h to obtain a mechanical mixed material, placing them in a tubular furnace, introducing inert gas Ar, pyrolyzing them at 550° C. for 4 h, and heating rate of 10° C. / min to obtain a black copper / nitrogen-carbon material powder;
[0045] S6, taking 200 mg of the copper / nitrogen-carbon material of step S5 and mixing it with 300 mg of sodium dihydrogen phosphate, transferring it into a micro ball mill, grinding and mixing it for 0.5 h to obtain a mechanical mixed material, placing it in a tubular furnace, passing inert gas Ar, pyrolyzing it at 700° C. for 2 h, and a heating rate of 10° C. / min to obtain a black copper / nitrogen-phosphorus-carbon material powder;
[0046] S7, taking 50 mg of the copper / nitrogen phosphorus-carbon material of step S6 and dispersing it in a mixed solution of 10 mL of deionized water and 15 mL of ethylene glycol, ultrasonically dispersing it for 0.5 h, adding 2.5 mg of potassium hypochloroplatinate, and further ultrasonically treating it for 0.5 h to form a solution D;
[0047] S8, the solution D of step S7 was transferred into a 100 mL standard hydrothermal kettle, placed in an oven at 120° C., and heated for 12 h. After the reaction was completed, it was naturally cooled to room temperature, centrifuged at 12000 rpm for 10 min, the precipitate was collected, and washed with a mixed solution of 10 mL deionized water and 5 mL ethanol, washed cumulatively 3 times, and freeze-dried in a freeze dryer at -40° C. for 6 h to obtain a black platinum alloy material powder;
[0048] S9, dispersing 5 mg of the black platinum alloy material powder in step S8 in a mixed solution of 180 μL of deionized water and 720 μL of isopropanol, adding 100 μL of Nafion adhesive, and performing ultrasonic treatment for 0.5 h every 0.5 h in an ultrasonic cell disruptor, for a cumulative treatment of 3 times, and further oscillating for 20 min in a vortex agitator to obtain a uniformly dispersed ink slurry containing platinum metal;
[0049] S10, the ink slurry containing platinum metal (platinum content of 0.15 mg) in step S9 pt / cm 2 ) was sprayed three times at a volume of 200 μL each time on a low-temperature (40°C) conductive carbon paper (1 cm 2 ), and each time interval is 0.5h to form a uniform catalytic layer;
[0050] S11, the conductive carbon paper (1 cm 2 ) and proton exchange membrane layer (Nafion 117 membrane, 1cm 2 ) was hot pressed at 130°C and 10 MPa for 3 min to form a multimodal pore structure platinum alloy electrode (platinum-copper / nitrogen-phosphorus-carbon-550).
[0051] Example 2
[0052] A method for hot working of a platinum alloy electrode with a multi-modal pore structure, comprising the following steps:
[0053] S1. Weigh 4.8 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and dissolve it in 20 mL of deionized water, and disperse it by ultrasonic for 0.5 h to form solution A. Weigh 3.2 g of benzenetricarboxylic acid (H3BTC) and dissolve it in 20 mL of ethanol, and disperse it by ultrasonic for 0.5 h to form solution B.
[0054] S2, solution A and solution B were mixed, ultrasonically mixed for 0.5 h, 4.8 g of polyvinyl pyrrolidone dispersant was added, and further ultrasonically treated for 1 h to form solution C;
[0055] S3, transfer solution C into a 100mL standard hydrothermal autoclave, place it in an oven at 140°C, heat it for 12h, and after the reaction is completed, naturally cool it to room temperature, centrifuge it at 12000rpm for 10min, collect the precipitate, wash it with a mixed solution of 10mL deionized water and 10mL ethanol, wash it cumulatively 3 times, and dry it in an oven at 80°C for 10h to obtain a blue metallic copper-based organic framework precursor powder;
[0056] S4, taking 400 mg of the blue precursor powder from step S3, grinding it thoroughly in a mortar, transferring it into a corundum boat, placing it in a tube furnace, introducing inert gas Ar, pyrolyzing it at 600° C. for 2 h, with a heating rate of 10° C. / min, to obtain a black copper / carbon material powder;
[0057] S5, taking 300 mg of the black copper / carbon material of step S4 and mixing it with 300 mg of urea, transferring it into a micro ball mill, grinding and mixing it for 0.5 h to obtain a mechanical mixed material, placing it in a tube furnace, passing inert gas Ar, pyrolyzing it at 600° C. for 4 h, and a heating rate of 10° C. / min to obtain a black copper / nitrogen-carbon material powder;
[0058] S6, taking 300 mg of the copper / nitrogen-carbon material of step S5 and mixing it with 450 mg of sodium dihydrogen phosphate, transferring it into a micro ball mill, grinding and mixing it for 0.5 h to obtain a mechanical mixed material, placing it in a tubular furnace, passing inert gas Ar, pyrolyzing it at 700° C. for 2 h, and a heating rate of 10° C. / min to obtain a black copper / nitrogen-phosphorus-carbon material powder;
[0059] S7, taking 100 mg of the copper / nitrogen phosphorus-carbon material of step S6 and dispersing it in a mixed solution of 20 mL of deionized water and 30 mL of ethylene glycol, ultrasonically dispersing it for 0.5 h, adding 5 mg of potassium hypochloroplatinate, and further ultrasonically treating it for 0.5 h to form a solution D;
[0060] S8, transfer the solution D of step S7 into a 100 mL standard hydrothermal kettle, place it in an oven at 120° C., heat it for 12 h, and after the reaction is completed, naturally cool it to room temperature, centrifuge it at 12000 rpm for 10 min, collect the precipitate, wash it with a mixed solution of 20 mL deionized water and 10 mL ethanol, wash it cumulatively 3 times, and freeze-dry it in a freeze dryer at -40° C. for 8 h to obtain a black platinum alloy material powder;
[0061] S9, dispersing 10 mg of the black platinum alloy material powder of step S8 in a mixed solution of 180 μL of deionized water and 720 μL of isopropanol, adding 100 μL of Nafion adhesive, and performing ultrasonic treatment for 0.5 h every 0.5 h in an ultrasonic cell disruptor, for a cumulative treatment of 3 times, and further oscillating for 20 min in a vortex agitator to obtain a uniformly dispersed ink slurry containing platinum metal;
[0062] S10, the ink slurry containing platinum metal (platinum content of 0.15 mg) in step S9 pt / cm 2 ) was sprayed three times at a volume of 100 μL each time on a low-temperature (40°C) conductive carbon paper (1 cm 2 ), and each time interval is 0.5h to form a uniform catalytic layer;
[0063] S11, the conductive carbon paper (1 cm 2 ) and proton exchange membrane layer (Nafion 117 membrane, 1cm 2 ) was hot pressed at 130°C and 10 MPa for 3 min to form a multimodal pore structure platinum alloy electrode (platinum-copper / nitrogen-phosphorus-carbon-600).
[0064] Example 3
[0065] A hot working forming method for a multi-modal pore structure platinum alloy electrode comprises the following steps:
[0066] S1. Weigh 5.4 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and dissolve it in 30 mL of deionized water, and disperse it by ultrasonic for 0.5 h to form solution A. Weigh 3.6 g of benzenetricarboxylic acid (H3BTC) and dissolve it in 30 mL of ethanol, and disperse it by ultrasonic for 0.5 h to form solution B.
[0067] S2, mixing solution A and solution B in step S1, ultrasonically mixing for 0.5 h, adding 5.4 g of polyvinyl pyrrolidone dispersant, and further ultrasonically treating for 1 h to form solution C;
[0068] S3, transfer the solution C in step S2 into a 100 mL standard hydrothermal autoclave, place it in an oven at 140°C, and heat it for 12 hours. After the reaction is completed, cool it naturally to room temperature, centrifuge it at 12000 rpm for 10 minutes, collect the precipitate, wash it with a mixed solution of 20 mL deionized water and 20 mL ethanol, wash it cumulatively 3 times, and dry it in an oven at 80°C for 12 hours to obtain a blue metallic copper-based organic framework precursor powder;
[0069] S4, taking 500 mg of the blue precursor powder from step S3, grinding it thoroughly in a mortar, transferring it into a corundum boat, placing it in a tube furnace, introducing inert gas Ar, pyrolyzing it at 600° C. for 2 h, with a heating rate of 10° C. / min, to obtain a black copper / carbon material powder;
[0070] S5, taking 400 mg of the black carbon material of step S4 and 400 mg of dicyandiamide, mixing them, transferring them into a micro ball mill, grinding and mixing for 0.5 h to obtain a mechanical mixed material, placing it in a tubular furnace, passing inert gas Ar, pyrolyzing it at 650° C. for 4 h, and a heating rate of 10° C. / min to obtain a black copper / nitrogen-carbon material powder;
[0071] S6, taking 500 mg of the copper / nitrogen-carbon material of step S5 and mixing it with 750 mg of sodium hypophosphite, transferring it into a micro ball mill, grinding and mixing for 0.5 h to obtain a mechanical mixed material, placing it in a tubular furnace, passing inert gas Ar, pyrolyzing it at 750° C. for 2 h, and a heating rate of 10° C. / min to obtain a black copper / nitrogen-phosphorus-carbon material powder;
[0072] S7, taking 150 mg of the copper / nitrogen phosphorus-carbon material of step S6 and dispersing it in a mixed solution of 20 mL of deionized water and 40 mL of ascorbic acid, ultrasonically dispersing it for 0.5 h, adding 10 mg of potassium hypochloroplatinate, and further ultrasonically treating it for 0.5 h to form a solution D;
[0073] S8, the solution D of step S7 was transferred into a 100 mL standard hydrothermal kettle, placed in an oven at 120° C., and heated for 12 h. After the reaction was completed, it was naturally cooled to room temperature, centrifuged at 12000 rpm for 10 min, the precipitate was collected, and washed with a mixed solution of 20 mL deionized water and 20 mL ethanol, washed cumulatively 3 times, and freeze-dried in a freeze dryer at -40° C. for 10 h to obtain a black platinum alloy material powder;
[0074] S9, dispersing 20 mg of the black platinum alloy material powder in step S8 in a mixed solution of 360 μL of deionized water and 540 μL of isopropanol, adding 100 μL of Nafion adhesive, and performing ultrasonic treatment for 0.5 h every 0.5 h in an ultrasonic cell disruptor, for a cumulative treatment of 3 times, and further oscillating for 20 min in a vortex agitator to obtain a uniformly dispersed ink slurry containing platinum metal;
[0075] S10, the ink slurry containing platinum metal (platinum content of 0.15 mg) in step S9 pt / cm 2 ) was sprayed three times at a volume of 100 μL each time on a low-temperature (40°C) conductive carbon paper (2 cm 2 ), and each time interval is 0.5h to form a uniform catalytic layer;
[0076] S11, the conductive carbon paper (2 cm 2 ) and proton exchange membrane layer (Nafion 117 membrane, 2cm 2 ) was hot pressed at 150°C and 13 MPa for 5 min to form a multimodal pore structure platinum alloy electrode (platinum-copper / nitrogen-phosphorus-carbon-650).
[0077] Comparative Example 1
[0078] A method for hot working of a platinum alloy electrode comprises the following steps:
[0079] Steps S1-S9 are consistent with those in Example 2;
[0080] S10, the ink slurry containing platinum metal (platinum content of 0.15 mg) of step S9 is pt / cm 2 ) was sprayed on a statically laid conductive carbon paper (1 cm 2 ), and each time interval is 0.5h to form a uniform catalytic layer;
[0081] S11, the conductive carbon paper (1 cm 2 ) and proton exchange membrane layer (Nafion 117 membrane, 1cm 2 ) was hot pressed for 3 min at conventional conditions of 80 ° C and 10 MPa to form a multimodal pore structure platinum alloy electrode (platinum copper / nitrogen phosphorus-carbon-600-S).
[0082] The platinum alloy electrodes prepared in Examples 1 to 3 and Comparative Example 1 were loaded into a mold with a serpentine gas flow channel, and a peak power density test was performed at an operating temperature of 80°C, a relative humidity of 100%, a cathode and anode gas flow rate of 2:1, and a back pressure of 1 bar. The values of their respective peak power densities are shown in Table 1.
[0083] Table 1 Peak power density test value table
[0084] project Peak power density Example 1 <![CDATA[203mW·cm -2 ]]> Example 2 <![CDATA[243mW·cm -2 ]]> Example 3 <![CDATA[212mW·cm -2 ]]> Comparative Example 1 <![CDATA[176mW·cm -2 ]]>
[0085] As shown in Table 1, the peak power density of the multimodal pore structure platinum alloy electrodes prepared in Examples 1 to 3 is maintained at 200 to 240 mW·cm -2 The peak power density of comparative example 1 is lower than 180mW·cm -2 This shows that layer-by-layer spraying low-temperature heat treatment is more conducive to the uniform dispersion of active substances on the electrode surface, thereby ensuring high battery power density.
[0086] Figure 1 The XRD diagrams of Examples 1-3 of the present invention show that the diffraction peaks of the multimodal porous structure platinum alloy electrodes prepared by different heat treatments are all located between the diffraction peaks of pure Pt (JCPDS04-0802) and Cu (JCPDS04-0836), which indicates that the transition metal-based precursors obtained by different heat treatments in a sulfuric acid medium are easy to undergo metal replacement with high-valent platinum and then alloyed.
[0087] Figure 2 This is the pore size distribution diagram of the platinum copper / nitrogen phosphorus-carbon-600 electrode prepared in Example 2. The results show that the layer-by-layer rotary spraying process is conducive to the formation of the electrode's hierarchical pore structure. Suitable pore size regulators and heat treatments achieve the coexistence of micropores, mesopores, and macropores in the electrode, thereby ensuring sufficient reactant accessibility and rapid electron exchange on the electrode surface.
[0088] Figure 3 This is the SEAD diagram of the platinum-copper / nitrogen-phosphorus-carbon-600 electrode prepared in Example 2. The results show that after high temperature and high pressure treatment, the crystallinity of all alloy crystal faces is low, and the electrode has a certain disordered structure and more deformation, which is conducive to better electrocatalysis.
[0089] Figure 4 Polarization curve and peak power density curve of the platinum copper / nitrogen phosphorus-carbon-600 electrode prepared in Example 2. The results show that the open circuit voltage of the electrode is 0.82 V and the peak power density is 243 mW·cm -2 , which is higher than the peak power density of the electrodes prepared in Examples 1 and 3 and Comparative Example 1, indicating that different heat treatment processes have different effects on the regulation of the electrode pore structure, and the optimal pore structure ratio has the optimal electrocatalytic performance.
[0090] The platinum alloy electrodes prepared in Example 2 and Comparative Example 1 were loaded into a mold with a serpentine gas flow channel, and impedance tests were performed at an operating temperature of 80°C, a relative humidity of 100%, a cathode and cathode gas flow rate of 2:1, and a back pressure of 1 bar. The test results are shown in Table 2.
[0091] Table 2 Test results
[0092] project Peak power density Example 2 <![CDATA[0.303Ω / cm 2 ]]> Comparative Example 1 <![CDATA[0.413Ω / cm 2 ]]>
[0093] As can be seen from Table 2, the impedance of the electrode of Comparative Example 1 is relatively large, which is attributed to the fact that, in the electrode obtained by hot pressing at conventional conditions of 80° C., the connection between the catalyst particles and Nafion is poor, which in turn leads to a decrease in the proton conductivity in the catalyst layer.
[0094] Therefore, the present invention adopts the above-mentioned hot working forming method of the platinum alloy electrode with multimodal pore structure, and realizes the construction of the multimodal pore structure of the platinum alloy electrode by adjusting the parameters of the gradual heat treatment process; and realizes the development of long-life platinum alloy electrodes by combining layer-by-layer spraying low-temperature heat treatment with high-temperature and high-pressure heat treatment.
[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A hot working forming method for a multi-modal pore structure platinum alloy electrode, characterized in that: The following steps are involved: S1. Dissolve copper nitrate trihydrate and benzenetricarboxylic acid in deionized water and ethanol respectively, and disperse by ultrasonic for 0.5 h to prepare solution A and solution B; S2, mixing the two solutions of step S1, ultrasonically mixing for 0.5 h, adding polyvinyl pyrrolidone dispersant, and further ultrasonically treating for 1 h to form solution C; S3, transferring the solution C in step S2 into a 100 mL standard hydrothermal kettle, placing it in an oven, and heating it for 12 h. After the reaction is completed, naturally cool it to room temperature, centrifuge it for 10 min, collect the precipitate, wash it with a mixed solution of deionized water and ethanol, and heat dry it to obtain a blue metallic copper-based organic framework precursor powder; S4, fully grinding the precursor powder of step S3 in a mortar, transferring it into a corundum boat, placing it in a tube furnace, introducing an inert gas, and performing high-temperature pyrolysis to obtain a black copper / carbon material powder; S5, mixing the black copper / carbon material of step S4 with one of melamine, urea and dicyandiamide, transferring the mixture into a micro ball mill, grinding and mixing for 0.5 h to obtain a mechanical mixed material, placing the mixture in a tubular furnace, introducing an inert gas, and performing high temperature pyrolysis to obtain a black copper / nitrogen-carbon material powder; S6, taking the copper / nitrogen-carbon material of step S5 and mixing it with sodium dihydrogen phosphate or sodium hypophosphite, transferring it into a micro ball mill, grinding and mixing it for 0.5h to obtain a mechanical mixed material, placing it in a tubular furnace, passing an inert gas, and performing high-temperature pyrolysis to obtain a black copper / nitrogen-phosphorus-carbon material powder; S7, dispersing the copper / nitrogen phosphorus-carbon material obtained in step S6 in a mixed solution of deionized water and ethylene glycol or deionized water and ascorbic acid, ultrasonically dispersing for 0.5 h, adding potassium hypochlorous platinum or chloroplatinic acid, and further ultrasonically treating for 0.5 h to form a solution D; S8, transferring the solution D in step S7 into a 100 mL standard hydrothermal kettle, placing it in an oven, and heating it for 12 h. After the reaction is completed, naturally cool it to room temperature, centrifuge it for 10 min, collect the precipitate, wash it with a mixed solution of deionized water and ethanol, and freeze-dry it to obtain a black platinum alloy material powder; S9, dispersing the black platinum alloy material powder in step S8 in a mixed solution of deionized water and isopropanol, adding Nafion adhesive, ultrasonically treating three times, and further oscillating in a vortex agitator for 20 minutes to obtain a uniformly dispersed ink slurry containing platinum metal; S10, spraying the ink slurry containing platinum metal in step S9 on the conductive carbon paper in batches and three times, and performing low-temperature drying to form a uniform catalytic layer; S11, compounding the conductive carbon paper loaded with the catalytic layer in step S10 with the proton exchange membrane layer, and subjecting them to high temperature and high pressure treatment to form a platinum alloy electrode with a multimodal pore structure.
2. The hot working forming method of a multi-modal pore structure platinum alloy electrode according to claim 1, characterized in that: In step S1, the mass ratio of copper nitrate trihydrate to benzenetricarboxylic acid is 3:2, and the volume ratio of deionized water to ethanol is 1:1; in step S2, the mass ratio of the added amount of polyvinyl pyrrolidone dispersant to copper nitrate trihydrate is 1:1; in step S3, the heating temperature is 140°C, the volume ratio of deionized water to ethanol is 1:1, and the drying temperature is 80°C.
3. The hot working forming method of a multi-modal pore structure platinum alloy electrode according to claim 1, characterized in that: In step S4, the inert gas is argon, the high temperature pyrolysis is pyrolysis at 600°C for 2h, and the heating rate is 10°C / min.
4. The hot working forming method of a multi-modal pore structure platinum alloy electrode according to claim 1, characterized in that: In step S5, the mass ratio of the black carbon material to one of melamine, urea and dicyandiamide is 1:1, the inert gas is argon, the high temperature pyrolysis is pyrolysis at 550-650°C for 4h, and the heating rate is 10°C / min.
5. The hot working forming method of a multi-modal pore structure platinum alloy electrode according to claim 1, characterized in that: In step S6, the mass ratio of the copper / nitrogen-carbon material to sodium dihydrogen phosphate or sodium hypophosphite is 1:1.5, the inert gas is argon, the high-temperature pyrolysis is pyrolysis at 700-750°C for 2h, and the heating rate is 10°C / min.
6. The hot working forming method of a multi-modal pore structure platinum alloy electrode according to claim 1, characterized in that: In step S7, the volume ratio of deionized water to ethylene glycol or ascorbic acid is 1:1.5-2, and the amount of potassium chloroplatinate or potassium hypochloroplatinate added is 5% of the mass of the copper / nitrogen phosphorus-carbon material.
7. The hot working forming method of a multi-modal pore structure platinum alloy electrode according to claim 1, characterized in that: In step S8, the heating temperature is 120°C, the volume ratio of deionized water to ethanol is 1:0.5-1, and the freeze-drying temperature is -40°C.
8. The hot working forming method of a multi-modal pore structure platinum alloy electrode according to claim 1, characterized in that: In step S9, the volume ratio of deionized water and isopropanol is 1:4, the mass fraction of Nafion adhesive is 5%, and the volume ratio of its addition amount to the polyvinyl pyrrolidone dispersant in step S2 is 1:0.
01. The ultrasonic treatment is performed for 0.5 h every 0.5 h, for a total of three times.
9. The hot working forming method of a multi-modal pore structure platinum alloy electrode according to claim 1, characterized in that: In step S10, the platinum content in the ink slurry containing platinum metal is 0.15 mg pt / cm 2 The rotary spraying is as follows: the conductive carbon paper is placed in a rotary machine at 200 rpm and 40° C. for spraying with a spray gun, with an interval of 0.5 h, and spraying layer by layer for three times in total.
10. The hot working forming method of a multi-modal pore structure platinum alloy electrode according to claim 1, characterized in that: In step S11, the area ratio of the catalyst layer to the proton exchange membrane layer is 1:1, the high temperature and high pressure treatment is 130-150° C., and the hot pressing is performed at 10-13 MPa for 3-5 min.
Citation Information
Patent Citations
Metal-loaded catalyst, battery electrode and battery
CA3149385A1
Non-noble metal catalytic electrode, film electrode and preparation method of non-noble metal catalytic electrode
CN109346728A
Platinum alloy catalyst, molten salt thermal preparation method and proton exchange membrane fuel cell
CN110518265A
Transition metal doped platinum-carbon catalyst as well as preparation method and application thereof
CN111129508A
One-dimensional porous platinum-containing alloy nanowire catalyst and preparation method thereof
CN111509236A